RETAIL NETWORKS AS A PLACE OF PURCHASE – THE EXAMPLE OF LARGE CITIES IN POLAND - Sojkin, Bogdan; Ankiel, Magdalena (Acta Scientiarum Polonorum. Oeconomia, 2019)
The article presents the results of the study investigating the purchasing behaviour of the residents of six large Polish cities (Warsaw, Wrocław, Katowice, Poznań, Białystok, and Gdańsk). Specifically, the study concentrates on the consumer shopping preferences with regard to grocery retail chains, pointing to the general differences and similarities, as well as gender- and age-specific tendencies. The study was conducted between 2016 and 2017 among 1970 respondents. This article also presents data from various reports of the research institutions from Poland and Europe: PMR, Nielsen, Ronald Berger, Euromonitor International, GfK Polonia. Despite problems with their comparability, they multidimensionally reflect the discussed issues that relate to the functioning of Polish retail trade, and they indirectly point to the purchasing behaviour of residents of Polish cities.